Young Children’s Conceptualisations of Kindness: A Thematic Analysis - Perkins, Nicole; Smith, Patrick; Chadwick, Paul (Frontiers in Psychology, 2022)
Although there is much interest in the development of prosocial behaviour in young children, and many interventions that attempt to cultivate kindness in children, there is a paucity of research exploring children’s lived experiences of kindness and including their voices. In this study, children’s understanding of kindness is approached through qualitative interviews using puppets. Interviews were conducted with 33 children aged 5-6 years in 3 UK schools. Through thematic analysis, 4 themes were developed: (a) doing things for others, (b) relating with others, (c) rules and values, and (d) kindness affects us. These themes are examined in light of current thinking on prosocial and sociomoral development, and several key insights are highlighted, including types of prosocial behaviour, social connection, kindness-by-omission and defending, in-group bias, universal kindness versus personal safety, self-image, and a desire to improve the condition of society. These findings have implications for future research on prosocial development and for the design of kindness-based interventions, as well as providing an ecologically valid method of inquiry for use with young children.